1986
DOI: 10.1111/j.1399-3054.1986.tb01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some metal chelators and light regimes on bioaccumulation and toxicity of Cd2+ in duckweed (Lemna gibba)

Abstract: A factorial culture experiment was designed to investigate the influence of light regimes and of some metal chelators on the accumulation of cadmium by Lemna gibba L. The plants were grown in a complete nutrient solution containing Cd2+ concentrations ranging from 0 to 27 μM with or without EDTA, ethylenediamine‐N,N′‐bis‐(o‐hydroxyphenylacetic acid) (EDDHA) or salicylic acid. Each experiment was run for eight days in 18 h:6 h light:dark or continuous light. An increase in the Cd2+ concentration in plants and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…The initial uptake of Cd by L. minor is in agreement with the data of Polar and Kucukcezzar (1986). Simultaneous exposure to Cd and LAS reduced DNA, RNA, protein and phospholipid synthesis compared with individual exposures.…”
Section: Discussionsupporting
confidence: 80%
“…The initial uptake of Cd by L. minor is in agreement with the data of Polar and Kucukcezzar (1986). Simultaneous exposure to Cd and LAS reduced DNA, RNA, protein and phospholipid synthesis compared with individual exposures.…”
Section: Discussionsupporting
confidence: 80%
“…1). Polar and Kü<;ükcezzar (1986) however concluded from their observations that the detoxificating effect of ED TA cannot be al ways interpreted in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease of cad mium toxicity by ED TA was described by Polar and Kü^ükcezzar (1986) for relative growth rates of duckweed and also by Greger andLindberg (1986 and1987) in the case of sugar content and growth of sugar beet. In the latter case toxicity symptoms depended on Cd and ED TA concentra tion in the nutrient medium.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the reported enhanced uptake of cations during illumination (McLean andWilliamson 1977, Weigel andJager 1980) and the continued translocation to the leaves in the dark period. Polar and Kucukcezzar (1986) reported that light duration alone or in combination with metal chelators affects the uptake of iroq, manganese, zinc and cadmium. Our results also revealed that in Cd-treated plants I Fe, Mn and Zn were generally higher as compared to controls (data not reported).…”
Section: Discussionmentioning
confidence: 99%